Genetic architecture of post-harvest tuber quality traits in bush yam (Dioscorea praehensilis Benth.) germplasm through association mapping - Adewumi, Adeyinka S.; Asare, Paul A.; Akintayo, Oluyemi Titilola; Adejumobi, Idris I.; Adu, Michael O.; Taah, Kingsley J.; Afutu, Emmanuel; Opoku, Vincent A.; Stanley, Adekemi E.; Akaba, Selorm; Mondo, Jean M.; Mushoriwa, Hapson; et al. (Frontiers in Horticulture, 2024)
Introduction Bush yam (Dioscorea praehensilis Benth.) is an important semi-domesticated food crop in West Africa. Limited information on the genetic architecture and its poor post-harvest tuber quality traits significantly hinder its use as food and source of income. Hence, dissecting the genetics underlying the expression of its post-harvest tuber quality traits is essential for establishing proper breeding schemes. Methods In this study, 138 D. praehensilis accessions collected in Ghana were sequenced using Diversity Array Technology (DArTSeq). The materials were profiled for dry matter content (DMC), tuber flesh oxidation (TBOXI) and for tuber flesh hardness (TBhard) during two cropping seasons. Results and discussion Diversity assessment using population structure, principal component analysis and hierarchical clustering methods revealed the presence of three major groups. Six genetic models were used for the trait association analysis using multiple random locus mixed linear model (MrMLM). Sixteen SNP markers distributed across the yam genome were identified to be associated with the evaluated traits. The associated SNP markers displayed a phenotypic variance ranged from 4.22% in TBHard to 16.92% in TBOXI. A total 25 putative candidate genes were identified around the SNP markers. The putative genes were identified to play key roles in tuber bulking, oxidative browning and starch hydroxylase. This study provides a valuable insight on the genetics underlying tuber quality traits in bush yam and opens avenues for developing genomic resources to improve D. praehensilis.